A review of the key demands for a football goalkeeper - West, J. (International Journal of Sports Science & Coaching, 2018)
This review evaluates previously published findings relating to the needs of a football goalkeeper during match performance. Whilst there has been much interest in some aspects of goalkeepers training, performance analysis and needs analysis, these have been from closed skill penalty situations or reported as comparisons with outfield players. This paper identifies important demands, assesses the implications for coaching and as a result highlights where the focus for effective future research should be to further enhance the development of goalkeeping performance.